Analisis Pengaruh Jumlah Tenaga Kerja, Investasi, Dan Konsumsi Rumah Tangga Terhadap Pertumbuhan Ekonomi Di Provinsi Bali - Zahirah, Ayu; Huda, Syamsul; Perdana, Putra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
An increase in the economy's ability to produce goods and services within a certain period of time is called economic growth. The number of workers, investment and household consumption are the main components that influence economic growth. These three factors are interrelated and play a role in determining the level of economic growth of a region. An increase in one of these factors can encourage the other two, creating a positive circle supporting sustainable economic growth. However, how these three components impact economic growth is also influenced by government policy and economic stability. Therefore, to achieve optimal economic growth, a balanced strategy is needed that considers these three components. This study aims to understand how the economic development of Bali Province is influenced by various variables, such as investment, number of workers, and household consumption. Researchers use quantitative methods.